Professional Values in Nursing and the Factors Which Affect Them: A Specific Example of a Private Hospital - Tuğba Mert; Serpil Çelik Durmuş (Baqiyatallah University of Medical Sciences, 2019)
Background: A professional is an individual who prefers a profession, is specially qualified in its technical aspects, and makes a living with the profession. Objective: This research was conducted to determine the professional values of nurses and the factors affecting them. Methods: This descriptive research evaluated a sample of 97 nurses working in a private hospital in Ankara, Turkey. Data was collected using the demographic form and professional values scale (PVS). Results: Among the nurses in the study sample, 43% had a graduate degree, 84.5% were staff nurses, and 37.2% were surgery, obstetrics, and cardiovascular surgery nurses. The mean score of professional values of nurses in this study was determined to be 4.20 ± 0.55. It was determined that professional values of nurses in the 34-year and older group, including male nurses, those usually working the day shift, those who chose the profession, those with memberships in associations, and those who participated in scientific meetings/seminars, had higher scores for professional values, but this finding was statistically insignificant (P > 0.05). Conclusion: The professional values of nurses was found to be above the middle level. In this light, it can be recommended, especially to managers, that training on professional values should be planned for nurses. It is also recommended that nurses receive undergraduate education and other comprehensive studies. In order to achieved a desired position in nursing, nurses must update regularly their scientific knowledge, participate in scientific meetings/seminars, and become members of professional associations.